Nusyuz and Domestic Violence in the Perspective of Islamic Law and Positive Law - Amberi, Mariani; Zakiyah, Zakiyah (International Journal of Law, Environment, and Natural Resources, 2024)
Nusyuz, which is textually understood as a wife who does not obey her husband, does not permit her husband when she wants to leave the house and the permissibility of husbands hitting their wives, which is considered legal by the Qur'an as stated in Q.S. An-Nisa: verse 34, improper interpretation, it leads to physical and psychological violence in the household and leads to disharmony and even triggers divorce. All forms of violence against spouses are not legalized in either the positive legal value system or Islamic law.  The purpose of this research is to discover how the concept of nusyuz and alternative solutions to nusyuz are allowed and their handling from the perspective of Islamic law and positive law. This research uses a library research method (normative law), and uses a descriptive analytical research type, and the research results are analyzed qualitatively, by examining existing regulations. Both women and men can commit Nusyuz, a husband can be said to have committed nusyuz if he relinquishes his responsibility towards his wife. Beatings carried out by husbands against nusyuz wives based on surah An Nisa 34, are not freely legalized but only to awaken and return the wife to obedience, not blows that cause pain and even injure. Positive Law contained in Law No. 23 of 2004 concerning Elimination of Domestic Violence is very firm in not allowing beatings and eliminating domestic violence and even criminal sanctions for perpetrators, both husband and wife.